Effectiveness of the SAS (Structural-Analytic-Synthetic) Method in Improving Beginning Reading Skills of Elementary School Students - Erna Khusniawati Khusniawati; Muhammad Muchsin Afriyadi (Elementary Education Journal, 2026)
Background: This study aimed to analyze the effectiveness of the SAS method in improving beginning reading skills of elementary school students. The study employed a Systematic Literature Review (SLR) method with a descriptive-narrative approach. Method: Data sources were obtained from scientific articles published between 2020–2026 indexed in Google Scholar and Scopus through the Publish or Perish application. The article selection process followed the PRISMA guidelines, including identification, screening, eligibility, and inclusion stages. Result: The findings showed that the SAS method effectively improved students’ ability to recognize letters, read syllables, words, and simple sentences gradually and meaningfully. The method also enhanced reading fluency, pronunciation, intonation, reading comprehension, learning motivation, and students’ self-confidence during the learning process. In addition, the effectiveness of the SAS method was supported by the use of various learning media such as letter cards, picture books, Pop-Up Books, PowerPoint, and digital teaching materials. Teachers also played an important role in guiding, motivating, and creating engaging learning environments. Implication: Therefore, the SAS method can be used as an effective alternative learning strategy to support the development of basic literacy skills in elementary school students.